A brief evaluation of the MOD17A2H product over a pasture in northeast Brazil. Issue 1 (2nd January 2021) - Ferreira, Rosaria R.; Santos E Silva, Cláudio M.; Bezerra, Bergson; Mendes, Keila R.; Mutti, Pedro; Campos, Suany; Marques, Thiago V.; P. Oliveira, Cristiano; Gonçalves, Weber; Espinoza, Nikolai; Difante, Gelson; Urbano, Stella A.
ABSTRACT: This research aims to provide a brief evaluation of remotely sensed estimates in representing gross primary production (GPP) over pasture in the Northeast Region of Brazil. We used GPP data measured in situ during a micrometeorological experiment performed in a pasture area located in the NEB region using the eddy covariance technique. Remotely sensed GPP was obtained through the MOD17A2H product of the Moderate Resolution Imaging Spectroradiometer (MODIS) sensor on board the Terra satellite. We concluded that the MOD17A2H product moderately represents surface-measured GPP in the studied site, highlighting the need for improvements in the quality of the remotely sensed GPP estimates over this type of ecosystem.